Teaching environment and sustainability: Experiences of a Vietnamese educator living in Canada - Tran, Thi Thuy Hang (Education and Development Research, 2024)
This research aims to address the question of whether Environment and Sustainability Education (ESE) is sustainable or not, considering the author's experiences as a lecturer in environmental sustainability programs in Vietnam and as a researcher/educator in a teacher education program in Canada. This study employs an autobiographical narrative approach rooted in experience. This study delves into the three-dimensional narrative spaces of temporality, sociality, and place to understand personal experiences and envision future narratives for international environmental sustainability education. Through this research, it is found that integrating teaching and training programs, familial curriculum making, and the sustainability of multi-species flourishing are holistic and long-term approaches to teaching environmental sustainability. The findings of this research highlight the importance of engaging various stakeholders in a wide-ranging collaborative process to discuss, debate, and analyze past and current pedagogical practices, as well as structural, programmatic, and economic challenges faced in environmental and sustainability education. Additionally, this research emphasizes the need to broaden perspectives by including the voices of Vietnamese educators teaching and conducting research in Canadian education.